Diet selection and food intake capacity of stall-fed sheep, goats and camels in relation to some physical properties of foods and their potential digestion in the rumen - Farid M.F.A.; Khamis H.S.; Abou El-Nasr H.M.; Ahmed M.H.; Shawket S.M. (Recent advances in small ruminant nutrition, 1997)
Four female camels, sheep and goats were individually fed ad libitum, barley grains, a commercial concentrate mixture and either clover hay or rice straw in separate feeders. Diet selection and food intake capacity were recorded. Dry packed volume, a suspension volume index, crude fibre content and indigestible crude fibre content remaining after 24 h in situ digestion of the foodstuffs were studied in a parallel laboratory experiment. Sheep consumed more barley grains than concentrate mixture whereas camels showed an opposite trend. Goats were practically similar to sheep, but they consumed the largest proportion of the roughage as compared to the other two species. Intake capacity per unit metabolic size was greater in sheep than in camels and goats. Across species, voluntary food intake was inversely related to crude fibre in the selected diets. However, all selected diets had similar packed volume values and suspension volume indices indicating the relationship between the fill properties of foods and the intake capacity of ruminant animals which is apparently valid across species.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)